Digital Learning Platforms as Facilitator for University-Business Collaboration in Logistics Management Curriculum Design - Novi Indah Susanthi; Mohammad Ali; Asep Herry Hernawan (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2026)
The logistics industry requires graduates who possess adaptive competencies and practical skills to respond effectively to dynamic industry demands, highlighting the importance of innovative and industry-oriented curriculum design. This study aims to analyze the implementation of a Logistics Management curriculum based on graduate competencies, with a particular focus on the application of learning strategies as a core component of the curriculum. A quantitative approach was employed using the fourth phase of Design and Development Research (DDR), which involved the experimental implementation of learning strategies in two logistics management classes following a needs analysis, competency identification, and curriculum design stages. The curriculum was developed based on five key components, competencies, learning objectives, content of materials, learning strategies, and evaluation. The results indicate that active learning approaches, including Project-based Learning (PjBL), Problem-based Learning (PBL), and Case Methods, positively support student engagement and competency development, students also reveal the need for more hands-on learning experiences, clearer instructional guidance, and stronger integration between theoretical knowledge and real-world logistics practices. This study contributes to innovation in logistics curriculum design by demonstrating how technology-enhanced active learning supported by digital learning platforms can function as enablers of industry-oriented education, strengthen university–business collaboration, and better prepare graduates for professional roles in the logistics sector.